Azolo[5, 1‐c][1, 2, 4]triazines and Azoloazapurines: Synthesis, Antimicrobial activity and in silico Studies. Issue 5 (1st February 2022) - Voinkov, Egor K.; Drokin, Roman A.; Fedotov, Victor V.; Butorin, Ilya I.; Savateev, Konstantin V.; Lyapustin, Daniil N.; Gazizov, Denis A.; Gorbunov, Evgeny B.; Slepukhin, Pavel A.; Gerasimova, Natalya A.; Evstigneeva, Natalya P.; Zilberberg, Natalya V.; et al.
Abstract: The present work reports on the synthesis of series of azolo[5, 1‐ c ][1, 2, 4]triazines and derivatives of azoloazapurines. The synthesized compounds were tested in vitro for antibacterial activity against N. gonorrhoeae and antimycotic activity against Trichophyton interdigitale, Epidermophyton floccosum, Microsporum canis and Candida albicans . It was found that 10 compounds of the series of 3‐nitroazolo[5, 1‐ c ][1, 2, 4]triazine‐4‐amines 4 exhibit high antibacterial activity (MIC≤15 μg/ml), but do not exhibit antimycotic activity. For compounds active against N. gonorrhoeae, a biological target was predicted from the pharmacophore search method and homologous modeling was carried out for it. The results of molecular docking using the constructed model of dihydrofolate reductase have a good correlation with in vitro tests. Refined docking showed the similarity of the leading compounds positions in the protein active site. The formation of stable non‐covalent bonds of the nitro group with the amino acid residues Lys34/Lys55 makes a major contribution to the orienting effect of ligands. Abstract : 3‐Nitroazolo[5, 1‐ c ][1, 2, 4]triazin‐4‐amine derivatives have shown high antibacterial activity against N. gonorrhoeae . The probable target for antibacterial azolotriazines is dihydrofolate reductase. The nitro group in azolotriazines has a great effect on antibacterial activity